Hubungan Kemampuan Kerja Dengan Kinerja Aparat Pemerintah di Kecamatan Kema Kabupaten Minahasa Utara - Rumapea, Patar; Pangemanan, Sofie E (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstract: The purpose of this research is to explain the relationship work ability and governmental apparatus performance. This research was conducted in the Kema sub district with 38 respondents sample. It used area sampling technique and stratified random sampling. Data was collected by using questionnaire technique in the form of questions measured by Likert scale. The analysis method used here is descriptive and correlation analysis by the simple regression analysis. Data analysis was conducted by using SPSS version 12,0 computer program. The results of this research indicated that: (1) based on the descriptive analysis shown that the work ability and governmental apparatus performance both are high category. (2) based on the simple regression analysis shown that the relationship between work ability and governmental apparatus performance is positive and significant. Based on this research may suggestion to the Head of Kema sub district that require to maintain and develop the attitude in work to all apparatus continually. Keywords: work ability, governmental apparatus performance.